A formação do município no Brasil nos pensamentos de Oliveira Vianna e Raymundo Faoro - Fabres, Paulo Roberto (2008)
This investigation aims at discussing the formation of the Brazilian municipal districts based on the ideas of Oliveira Vianna, as they were published in his book “Populações Meridonais do Brasil e Instituições Políticas Brasileiras” confronted to those in “Os Donos do Poder”, by Raymundo Faoro, which discusses the formation of the Brazilian political patronage. From the comparative analysis of both authors, it is highlighted their main individual ideas with regard to the development of the municipal districts in Brazil, from the historical periods known as “Colonial Brazil” to the first half of the XIX century. In this study, it is discussed the interpretations of both Faoro and Vianna specifically concerning the influence of the early Portuguese juridical and institutional framework throughout the political formation of the Brazilian municipal districts, and also the adaptations by which the municipal institutions were formed under those new political and social environment. Finally, it is pointed out the divergences as well as the convergences of the ideas of both authors regarding the genesis and the development of the modern Brazilian municipal institutions.